(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Although prescription use is common during pregnancy, the human teratogenic risks are undetermined for quite 90% of drug treatments approved within India during the past decades. A selected birth defect may have its origins through multiple mechanisms and possible exposures, including medications. A specific pathogenic process may end in several outcomes depending upon factors like embryonic age at which a drug is run, duration and dose of exposure and genetic susceptibility. This research focuses on the teratogenic mechanisms with their effects associated with kinds of natural also as synthetic substances. Mechanisms were included only if they are associated with major structural birth defects and medications that are used relatively frequently by women of reproductive age. Identifying teratogenic mechanisms won’t only be relevant for etiologic and post marketing research, but also can have implications for drug development and prescribing behavior for girls of reproductive age, especially since combinations of seemingly unrelated prescription and over the counter medications may utilize similar teratogenic mechanisms with a resultant increased risk of birth defects